2012
DOI: 10.1039/c2dt00020b
|View full text |Cite
|
Sign up to set email alerts
|

Pushing the limit: synthesis, photophysical and DNA binding studies of a NIR-emitting Ru(ii)-polypyridyl probe with ‘light switch’ behaviour

Abstract: The new Ru(II) polypyridyl complex 1 was synthesised using microwave irradiation from the new polypyridyl ligand 2 'DipyTAP', and its photophysical properties, and DNA binding abilities were investigated using various spectroscopic techniques; and 1 was shown to act as a 'NIR molecular light switch' for DNA with an emission window between 680 and 860 nm.Luminescent transition metal coordination complexes that possess DNA binding abilities have been the subject of growing interest in recent times by virtue of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
0
13
1
Order By: Relevance
“…However, successive additions of DNA (0.00–90 μM) into Ru2 (2.33 μM) elicited slight emission enhancement by a factor of 1.32 along with a blue shift by 30 nm from 700 to 670 nm (see Figure b). This large DNA binding induced blue shift is not common in comparison to previously reported near-IR- and visible-light-emitting Ru complex based DNA intercalators and groove binders and has not been observed for any DNA electrostatic binders. , This DNA binding induced spectral behavior of Ru2 is in sharp contrast to that of [Ru­(Hpip) 3 ] 2+ (Hpip = 2-phenylimidazo­[4,5- f ]­[1,10]-phenanthroline), which showed almost unchanged emission and UV–vis absorption spectral changes during the DNA titrations and was claimed to be a DNA electrostatic binder; the lack of intercalation or groove binding could be understood by the fact that [Ru­(Hpip) 3 ] 2+ contains three long and large Hpip ligands, which are difficult to accommodate efficiently in the DNA groove, although [Ru­(bpy) 2 (Hpip)] 2+ was evidenced to be a DNA intercalator . The aforementioned UV–vis absorption and emission spectral changes induced by binding of the DNA to Ru1 and Ru2 provide evidence that electrostatic DNA binding modes of these two complexes could be excluded, but their definite DNA binding modes with respect to intercalation or groove binding need further investigations.…”
Section: Resultscontrasting
confidence: 51%
“…However, successive additions of DNA (0.00–90 μM) into Ru2 (2.33 μM) elicited slight emission enhancement by a factor of 1.32 along with a blue shift by 30 nm from 700 to 670 nm (see Figure b). This large DNA binding induced blue shift is not common in comparison to previously reported near-IR- and visible-light-emitting Ru complex based DNA intercalators and groove binders and has not been observed for any DNA electrostatic binders. , This DNA binding induced spectral behavior of Ru2 is in sharp contrast to that of [Ru­(Hpip) 3 ] 2+ (Hpip = 2-phenylimidazo­[4,5- f ]­[1,10]-phenanthroline), which showed almost unchanged emission and UV–vis absorption spectral changes during the DNA titrations and was claimed to be a DNA electrostatic binder; the lack of intercalation or groove binding could be understood by the fact that [Ru­(Hpip) 3 ] 2+ contains three long and large Hpip ligands, which are difficult to accommodate efficiently in the DNA groove, although [Ru­(bpy) 2 (Hpip)] 2+ was evidenced to be a DNA intercalator . The aforementioned UV–vis absorption and emission spectral changes induced by binding of the DNA to Ru1 and Ru2 provide evidence that electrostatic DNA binding modes of these two complexes could be excluded, but their definite DNA binding modes with respect to intercalation or groove binding need further investigations.…”
Section: Resultscontrasting
confidence: 51%
“…An interesting study has shown that complex 47 acts as an efficient NIR molecular light switch. 57 On the basis of several spectroscopic techniques, it is suggested that this complex is inserted edgewise into the grooves of DNAalthough the authors did not discard the possibility of partial intercalation.…”
Section: Non-covalent Interactions Of Metal Complexes With Dnamentioning
confidence: 99%
“…Complexes 55-60 are emissive and their luminescence is enhanced upon interaction with DNA -with some selectivity for quadruplex over duplex DNA. The cellular uptake of one of them (57) has been studied by real-time living cell microscopy, which showed it localises in the nucleus. 66 Another interesting feature of complex 57 is that its L stereoisomer has higher affinity towards quadruplex DNA than the D stereoisomer.…”
Section: Non-covalent Interactions Of Metal Complexes With Dnamentioning
confidence: 99%
“…74 A Ru(phen) 2 complex of a dipyridyltetraazaphenanthrene acts as a NIR molecular light switch for DNA with emission at B780 nm in the presence of single stranded DNA. 75 Ru(bpy) 2 , Os(bpy) 2 and Ir(2-(p-tolyl)pyridine) 2 complexes of diarylamine-bpy-anthraquinone conjugate VI exhibit long-lived charge separated states with lifetimes of 80 ns to 1 ms upon excitation of the metallic chromophore. 78 [Ru(dcb) 2 ] complexes with a pyrene appended bpy ligand show dcb centred 3 MLCT emission at pH 0.…”
Section: Annual Reports a Reviewmentioning
confidence: 99%